Influence of Prebiotics Supplementation on Lipid Profile of Broilers - Kannan, M.; Karunakaran, R.; Balakrishnan, V.; Prabhakar, T.G. (International Journal of Poultry Science, 2005)
The prebiotic - Mannanoligosaccharide (MOS) was extracted from yeast and copra meal and evaluated for their prebiotic potentiality on serum lipid profile and abdominal fat pad. The treatment groups were fed with basal diet (T1). The basal diet was supplemented with extracted MOS from yeast [@ 0.5 g/kg (T2); 1 g/kg (T3)] and from copra meal [@ 1 g/kg (T4); 1.5 g/kg (T5)] and with MOS sources such as yeast [MOS equivalent of 0.5 g/kg (T6); 1 g/kg (T7)] and copra meal [MOS equivalent of 1 g/kg (T8); 1.5 g/kg (T9)]. A broiler trial was conducted for a period of five week. The results revealed that serum total cholesterol concentration was significantly (P< 0.01) lowered by 10, 12 and 12 per cent in birds fed with T2, T6 and T7 diet respectively when compared with control diet in broiler chicken at 5th week of age. There was no significant difference in serum HDL cholesterol of birds fed with extracted MOS / MOS equivalent source except T6 which was found significantly (P< 0.05) lower than control groups. LDL cholesterol level was similar in all treatment groups except higher value observed in T5(91.69 ±13.54mg/dl). The abdominal fat pad (percentage of live weight) was found to be significantly (P< 0.01) lowest in T3. This study indicates that the supplementation of prebiotic extracted from yeast at 0.5 and 1g/kg and copra meal at 1.5g/kg and yeast source at 1g/kg level respectively reduced the abdominal fat content.